ANALISIS PREFERENSI SISWA MELANJUTKAN STUDI KE MTSN KECAMATAN KUOK KABUPATEN KAMPAR TP. 2014/2015. - Misdona '; Zulfan Saam Zulfan Saam; Elni Yakub Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Thisresearch aims to: (a) Analyzeaspects ofthe internalthatbecomethe preferenceof studentschoosing MTSN, (b) AnalyzeaspectsExternalthatbecomethe preferenceof studentschoosing MTSN, (c) Analyzingthe category ofinternal factorsthatbecomethe preferenceof studentschoosing MTSN, (d) Analyzingthe category ofexternal factorsintothe preferencesof studentschoosing MTSN. The method usedinthisstudyis adescriptivestudy, thetechnique ofsaturatedsamples. Theresults ofthis study are: (a) aspects ofthe internalthatbecamepreferencestudentschoose MTSN isbecausewant toexplorethe religion of Islam. (b) aspects of theexternal factorsthatbecomePreferencesstudentschoose MTSN islocatedon aspectsThe desireof parents, (c) Categoryinternalbecomethe preferenceof studentschoosing MTSN at the high category, (d) Categoryexternal becomepreferencestudentschoose MTSN in low category. Keywords: Preferences, MTSN